1981
DOI: 10.1177/000992288102000505
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid White Blood Cell Counts and Lactic Acid Dehydrogenase in Enterovirus Type 71 Meningitis

Abstract: An outbreak of aseptic meningitis involving 36 children is described. Enterovirus type 71, a recently recognized cause of central nervous system and systemic illness in children, was found to be the responsible agent. On initial lumbar puncture, cerebrospinal fluid (CSF) polymorphonuclear (PMN) cell predominance was seen in 64%, and greater than 200 CSF white blood cells (WBC)/mm3 was seen in 25% of these patients. Fifty-four per cent of the patients subjected to repeat lumbar puncture and a significant rise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Our results are conflicting regarding typical CSF in EV-A71 CNS infection. In one study in children with EV-A71 meningitis, CSF showed a neutrophil predominance in 64% of cases and >200 WBC/ mm 3 in 25% (Goldberg and Weiner, 1981) In a case series of 29 children with EV-A71 fatal infections, lymphocytic predominance was reported in 11/12 patients with pleiocytosis on lumbar puncture (Chan et al, 2000). Our results confirm previous findings on the association between EV-A71 related pulmonary oedema and high neutrophil count or hyperglycemia (Chang et al, 1999;Lin et al, 2002) but also highlights the higher rate of neutrophilic CSF in PO patients and lymphocytic CSF in encephalitis patients .…”
Section: Discussionmentioning
confidence: 94%
“…Our results are conflicting regarding typical CSF in EV-A71 CNS infection. In one study in children with EV-A71 meningitis, CSF showed a neutrophil predominance in 64% of cases and >200 WBC/ mm 3 in 25% (Goldberg and Weiner, 1981) In a case series of 29 children with EV-A71 fatal infections, lymphocytic predominance was reported in 11/12 patients with pleiocytosis on lumbar puncture (Chan et al, 2000). Our results confirm previous findings on the association between EV-A71 related pulmonary oedema and high neutrophil count or hyperglycemia (Chang et al, 1999;Lin et al, 2002) but also highlights the higher rate of neutrophilic CSF in PO patients and lymphocytic CSF in encephalitis patients .…”
Section: Discussionmentioning
confidence: 94%
“…CSF glucose content is usually normal but can be diminished in up to 18% of cases (137,157). The measurement of CSF concentrations of C-reactive protein, lactic acid dehydrogenase, and alpha interferon to differentiate between bacterial and viral meningitis is not generally feasible, although some studies suggest that these tests may be helpful (1,2,34,50,62,111).…”
Section: Enterovirusesmentioning
confidence: 99%
“…Non-specific assays such as c-reactive protein (Corral1 et af. 1981, Peltola 1982) and lactic acid dehydrogenase (Goldberg and Weiner 1981) have been proposed as means of determining viral versus bacterial etiology of meningitis. However, these have not been found sensitive or specific enough to gain routine use in the management of infants with meningitis (Chonmaitree et a/.…”
Section: Problemsmentioning
confidence: 99%